50 impressive kids and their amazing (and true!) stories - Mitchell, Saundra (They did what?, 2016)
"From Stevie Wonder to Emma Watson, and Pocahontas to Pablo Picasso, 50 amazing kids who shaped history! A collection of biographies profiling some of the most influential kids in history and today. Prodigies, proteges, and kids with huge ambition, these youngsters prove that fulfilling your dreams and making a difference in the world isn't just for grown-ups. Some of the most phenomenal musicians, inventors, athletes, authors, actors, and even world leaders achieved greatness during their childhood years, beating the odds and making their mark on history. With loads of facts and trivia, activities, jokes, and a complete glossary, discover fifty of the most inspiring, impressive, incredible kids!"--